2016
DOI: 10.19044/esj.2016.v12n1p488
|View full text |Cite
|
Sign up to set email alerts
|

Police Use Of Excessive Force: A Case Study Of Lethal (Deadly) Force

Abstract: Two African-American civilians, Sean Bell and Amadou Bailo Diallo, suffered tragic deaths as a result of use of lethal force by the police. This case study presents an in-depth analysis of the determinants that affected the officers' use of lethal force with regard to the above mentioned cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…On the other hand, there was greater variation among the articles in relation to sample size, unit of analysis, time periods, and methodologies. For example, sample sizes ranged from two case studies (Kargin, 2016) to 30 officer-involved shootings (Parent, 2011) to 23,578 police-related homicides (Finch et al, 2019). We also observed variation in the unit of analysis examined, as studies examined officer- ( n = 8), agency- ( n = 5), incident- ( n = 57), county- ( n = 3), city- ( n = 5), state- ( n = 2), and country-level ( n = 2) differences, among others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there was greater variation among the articles in relation to sample size, unit of analysis, time periods, and methodologies. For example, sample sizes ranged from two case studies (Kargin, 2016) to 30 officer-involved shootings (Parent, 2011) to 23,578 police-related homicides (Finch et al, 2019). We also observed variation in the unit of analysis examined, as studies examined officer- ( n = 8), agency- ( n = 5), incident- ( n = 57), county- ( n = 3), city- ( n = 5), state- ( n = 2), and country-level ( n = 2) differences, among others.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars have found that in police-citizen encounters in which a subject is armed with a gun or weapon and an officer is injured, the likelihood of officer-involved shootings (Davies, 2017; Jordan et al, 2020; Morgan et al, 2020; Taylor, 2020; Wheeler et al, 2018; Worrall et al, 2018), the number of shots fired by the police officer (White & Klinger, 2012), and the lethality of an officer-involved shooting (Fridel et al, 2020; Jennings et al, 2020; Johnson et al, 2019), all significantly increase. Researchers have also found a significant positive association between officer-involved shootings and police officers with prior police misconduct or citizen complaints (Kargin, 2016; Ridgeway, 2016; Worrall et al, 2018; Zhao & Papachristos, 2020), police militarization (Lawson, 2019), levels of household gun ownership (Hemenway et al, 2019), mental illness (DeGue et al, 2016; Lord, 2014), and Western states (Helms & Costanza, 2020; Johnson, 2013; Willits & Nowacki, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation